2007
DOI: 10.1089/cpb.2006.9932
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Brain Potentials in Response to Smoking-Induced Stimuli in Smokers

Abstract: Changes in P300 amplitude were used as an indicator of reactivity to smoking-related stimuli in smokers. The amplitude of P300--a component of event-related brain potentials (ERPs) elicited by 10 smoking-related (craving), 10 antismoking (aversive) and 10 neutral stimuli-- was recorded in smokers (n=10) and nonsmokers (n=10). Electroencephalography (EEG) data were obtained by the Laxtha EEG-monitoring device in the EEG recording room, and were recorded at F3, F4, C3, and C4. Three-way repeated-measures analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…This can be explained by the symbolic communication style characterizing the "awarded" PSA. In addition, the statistically significant effect of the spot category, as well as the same tendency of the image category, are in line with the results presented in previous studies, where the right or left hemisphere activation-reflected by the different P300 amplitude variation-was modulated by exposure to neutral, promoting, and contrasting smoking messages stimuli 75 .…”
Section: Discussionsupporting
confidence: 91%
“…This can be explained by the symbolic communication style characterizing the "awarded" PSA. In addition, the statistically significant effect of the spot category, as well as the same tendency of the image category, are in line with the results presented in previous studies, where the right or left hemisphere activation-reflected by the different P300 amplitude variation-was modulated by exposure to neutral, promoting, and contrasting smoking messages stimuli 75 .…”
Section: Discussionsupporting
confidence: 91%
“…The P3 component has frequently been used to assess cue reactivity among individuals with substance use disorders (SUDs) (for a comprehensive review, see Littel, Euser, Munafo, & Franken, 2012), including nicotine dependence (Jang, Lee, Yang, & Lee, 2007; Littel & Franken, 2007, 2011a, 2011b, 2012; McDonough & Warren, 2001; Versace et al, 2012; Versace et al, 2011; Versace et al, 2010; Warren & McDonough, 1999). A recent meta-analysis indicated that the P3 is of significantly larger amplitude in response to drug-related stimuli vs. neutral stimuli, and that the difference in amplitude between drug-related and neutral stimuli is significantly larger among individuals with SUDs relative to controls without SUDs, indicating preferential attention to drug-related stimuli in SUDs (Littel, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In smokers and non-smokers groups, a different response lateralization between the two hemispheres, in the present study indexed by positive (left) and negative (right) frontal alpha asymmetry values, has been already showed. Specifically, it has been shown an increased P300 amplitude produced by smokers in the right hemisphere in response to both tobacco promoting and antismoking images, vice versa in the left hemisphere by non-smokers (Jang et al, 2007). These results appear in contrast with the present data showing a higher response in the left hemisphere in HS and in the right hemisphere in the NS groups, nevertheless this could be attributable to the different definition of smokers between the two researches (i.e., more than two cigarettes per day, while in the present study participants have been divided between HS and LS on the basis of the threshold of five cigarettes per day) and to the different age of the experimental sample (mean age 30.6 years ± 7.5 in Jang et al’s (2007) study, while 18.308 ± 2.726 years in the present research).…”
Section: Discussionmentioning
confidence: 99%
“…Through such neuroscience techniques several aspects related to the commerce can be investigated: target population’s gender (Vecchiato et al, 2014a; Cartocci et al, 2016a), culture (Han and Shavitt, 1994; Vecchiato et al, 2011a) and age (Cherubino et al, 2016a); fragments of interest (Vecchiato et al, 2010, 2011b, 2014a); the brand (Paulus and Frank, 2003); the price (Reimann et al, 2011); scenes targeting and speaker’s gender (Cherubino et al, 2016b); purchasing attitudes of the subjects (Knutson et al, 2007) and pre-retail testing (Baldo et al, 2015). The capability of EEG techniques to detect different patterns between smokers and non-smokers have been already provided from event related potentials (ERP) studies, in which the amplitude of the P300 resulted lower in smokers than in non-smokers (Anokhin et al, 2000; Jang et al, 2007; Guney et al, 2009). Importantly, this difference can be affected by the stimulus category, as evidenced by an ERP study in which it has been shown a signicant smoking cue-reactivity of the P412, a P300-like wave correlation with unpleasantness-pleasantness in reaction to the cue (Warren and McDonough, 1999).…”
Section: Introductionmentioning
confidence: 99%